Measurement of the signal from a cultured cell using a high-T-c SQUID - Tanaka, S.; Yoshida, S.; Eki, T.; Aspanut, Z.; Oshita, M.; Uchida, M.; Natsume, M.; Tanaka, N. (2003)
Stem cells in developing tissues give rise to the multiple specialized cell types that make up the heart, lung, skin, and other tissues. For scientists, it is important to know the stages of stem cell development. We propose a new method to obtain knowledge of the cell development stages by using a high-T-c SQUID magnetometer. In the first step of the research, we used Wister rat myocardial cells incubated for 12-14 days in a culture dish as a sample, which were not derived from stem cells. With the cells we tried to measure the signal using a SQUID magnetometer. We were able to measure the magnetic signals, which may be generated by ion transport through the cell membrane. A beat signal with a period of 0.6 s was observed. The peak-to-peak value was about 400 pT. This showed good agreement with the result of microscopic observation.